Myc Supports Self-Renewal of Basal Cells in the Esophageal Epithelium - Hishida, Tomoaki; Vazquez-Ferrer, Eric; Hishida-Nozaki, Yuriko; Takemoto, Yuto; Hatanaka, Fumiyuki; Yoshida, Kei; Prieto, Javier; Sahu, Sanjeeb Kumar; Takahashi, Yuta; Reddy, Pradeep; O’Keefe, David D.; Rodriguez Esteban, Concepcion; et al. (Frontiers in Cell and Developmental Biology, 2022)
It is widely believed that cellular senescence plays a critical role in both aging and cancer, and that senescence is a fundamental, permanent growth arrest that somatic cells cannot avoid. Here we show that Myc plays important role on self-renewal of esophageal epithelial cells, contributing to their resistance to cellular senescence. Myc is homogeneously expressed in basal cells of the esophageal epithelium and Myc positively regulates their self-renewal by maintaining their undifferentiated state. Indeed, Myc knockout induced a loss of the undifferentiated state of esophageal epithelial cells resulting in cellular senescence while forced MYC expression promoted oncogenic cell proliferation. A superoxide scavenger counteracted Myc knockout-induced senescence, therefore suggesting that a mitochondrial superoxide takes part in inducing senescence. Taken together, these analyses reveal extremely low levels of cellular senescence and senescence-associated phenotypes in the esophageal epithelium, as well as a critical role for Myc in self-renewal of basal cells in this organ. This provides new avenues for studying and understanding the links between stemness and resistance to cellular senescence.